Challenges and perspectives of organic farming in the 21st century - Golijan-Pantović Jelena (Acta Agriculturae Serbica, 2025)
Organic farming is experiencing significant global growth, with an increase in the area under organic production, the number of producers, and the market value of organic products. In 2023, organic farming covered 98.9 million hectares worldwide, while the organic product market exceeded 136 billion euros. This paper analyzes the current status of organic farming, the main challenges it faces in the 21st century, and the opportunities for its further development. Key challenges include lower yields compared to conventional agriculture, limited land availability, the consequences of climate change, high certification costs, and a lack of infrastructure and education. Additionally, consumer trust and competition with conventional farming systems pose further obstacles to the expansion of organic production. On the other hand, technological innovations, policy support and subsidies, the development of local markets, and consumer education offer opportunities for improving the sector. Precision agriculture, biological pest control, artificial intelligence, and agroecological approaches can contribute to increasing the productivity and resilience of organic systems. Furthermore, investments in infrastructure, simplified certification processes, and greater consumer involvement through educational campaigns are key factors for the long-term success of organic farming. It is concluded that the further development of organic farming requires coordination between government institutions, research organizations, and the private sector. Through innovation, education, and strategic support, organic farming can become a key pillar of sustainable development and the preservation of natural resources for future generations.